PENGARUH PENGETAHUAN DASAR EKONOMI DAN PERSEPSI LINGKUNGAN PONDOK PESANTREN TERHADAP POLA KONSUMSI SANTRIWAN IIS MA PONDOK PESANTREN NURUL ULUM MALANG - Mohaswin Rizki Ilham; Sapir Sapir (Jurnal Pendidikan Ekonomi, 2017)
Education in boarding schools having own way educate school tuition or of the so-called santri , santri learned about general studies and live a daily lives in the neighborhood pondok pesantren .Consumption patterns in boarding schools influenced by many factors such as knowledge basic economic, and environment boarding schools. Population in research it is a whole santriwan IIS MA Pondok Pesantren Nurul Ulum poor were 57 santriwan .Sample in this research using all population. The kind of research that is used is research eksplanasi , with technical linear regression analysis worship of idols .Variable research among other: the economics basic knowledge (X1), perception of boarding school (X2), and consumption behavior (Y). Using techniques data collection tests and survey or questionnaire. The conclusion of research is (1) basic knowledge economy influential significantly to consumption patterns santriwan IIS MA boarding schools Nurul Ulum Malang. (2) boarding schools environmental effect significantly to consumption patterns santriwan IIS MA boarding schools Nurul Ulum Malang. Basic knowledge economy and the environment boarding schools significant against consumption patterns santriwan IIS MA boarding schools Nurul Ulum Malang. Because of that, Expected the boarding schools able to guide santriwan for better again in consumption. DOI: https://dx.doi.org/10.17977/UM014v10i22017p161